'Community' in the sociology of religion: The case of Britain. (June 2015) - Beckford, James A
The author's aim is to offer some critical observations on usage of the terms 'community' and 'faith community'. The central argument is that 'community' is a weasel word that occurs frequently in discourses at the levels of everyday life, public policy-making, welfare services and social scientific analysis. The article begins by reviewing relatively uncontentious uses of 'community'. The second section of the article analyses the UK government's usage of the term 'faith community' in policy documents since 1997. And the third section explores two particularly problematic issues: on the one hand a tension that arises within official discourses about faith communities and, on the other, the UK government's practice of treating faith communities as if they were undifferentiated collectivities. The conclusion urges sociologists of religion to avoid uncritically reproducing official discourses about faith communities.